PRESTASI BELAJAR MATEMATIKA: DAMPAK AGRESIVITAS DAN AKTIVITAS BELAJAR SISWA - Aprisal, Aprisal; Husnaeni; Mahmud, Nurfadilah (Universitas Sulawesi Barat, 2025)
This research aims to identify the impact of aggressive behavior and student learning activities on mathematics learning achievement. The population in this study were students of class VIII of SMP Negeri 5 Tinambung. The sampling technique used was a saturated sampling technique by taking all populations as research samples. The number of research samples was 54 students. The research data collection instruments consisted of an aggressive behavior questionnaire, a learning activity questionnaire, an observation sheet, and a mathematics learning achievement test. The research data were analyzed using multiple regression tests to determine the impact of aggressive behavior and student learning activities simultaneously on students' mathematics learning achievement. The results of the data analysis showed that aggressive behavior and learning activities had an impact on students' mathematics learning achievement